Genetically stable infectious Schmallenberg virus persists in foetal envelopes of pregnant ewes. - Poskin, Antoine; Martinelle, Ludovic; Yves Van der Stede; Saegerman, Claude; Brigitte Cay; Nick De Regge (J Gen Virol, 2017)
Schmallenberg virus (SBV) is a recently emerged vector-borne virus, inducing congenital defects in bovines, ovines and caprines. Here we have shown that infectious SBV is capable of persisting until the moment of birth in the foetal envelopes of ewes infected with SBV-infectious serum at day 45 (1/5 positive) and 60 (4/6 positive) of gestation. This persistence of at least 100 days is a new aspect of the SBV pathogenesis that could help to explain how SBV overwinters the cold season in temperate climate zones. Furthermore, sequencing of the M segment shows that the persisting virus in the foetal envelopes is genetically stable since only a few mutations compared to the inoculum were found. This supports the hypothesis that persisting virus could start the infection of new hosts. Finally, neutralization tests showed that infectious SBV present in the foetal envelopes at birth can be neutralized by the humoral immunity present in the infected ewes.
Keywords: Animals; Antibodies, Viral; Base Sequence; Bunyaviridae Infections; Chorion; Female; Orthobunyavirus; Placenta; Pregnancy; RNA, Viral; Sequence Analysis, RNA; Sheep; Sheep Diseases